Integration of antimicrobial peptides with gold nanoparticles as unique non-viral vectors for gene delivery to mesenchymal stem cells with antibacterial activity. (October 2016) - Peng, Li-Hua; Huang, Yan-Fen; Zhang, Chen-Zhen; Niu, Jie; Chen, Ying; Chu, Yang; Jiang, Zhi-Hong; Gao, Jian-Qing; Mao, Zheng-Wei
Abstract: Gold nanoparticles (AuNPs) have emerged as attractive non-viral gene vectors. However their application in regenerative medicine is still limited partially due to a lack of an intrinsic capacity to transfect difficult-to-transfect cells such as primary cells or stem cells. In current study, we report the synthesis of antimicrobial peptide conjugated cationic AuNPs (AuNPs@PEP) as highly efficient carriers for gene delivery to stem cells with antibacterial ability. The AuNPs@PEP integrate the advantages of cationic AuNPs and antibacterial peptides: the presence of cationic AuNPs can effectively condense DNA and the antimicrobial peptides are essential for the cellular & nucleus entry enhancement to achieve high transfection efficiency and antibacterial ability. As a result, antimicrobial peptides conjugated AuNPs significantly promoted the gene transfection efficiency in rat mesenchymal stem cells than pristine AuNPs, with a similar extent to those expressed by TAT (a well-known cell-penetrating peptide) modified AuNPs. More interestingly, the combinational system has better antibacterial ability than free antimicrobial peptides in vitro and in vivo, possibly due to the high density of peptides on the surface of AuNPs. Finally we present the concept-proving results that AuPs@PEP can be used as a carrier for in vivo gene activation in tissue regeneration, suggesting its potential as a multifunctional system with both gene delivery and antibacterial abilities in clinic.